Global time-trend analysis and projections of disease burden for neuroblastic tumors: a worldwide study from 1990 to 2021 - Yinjie Tao; Weishi Cheng; Hongnan Zhen; Jing Shen; Hui Guan; Zhikai Liu (Italian Journal of Pediatrics)
Abstract Background Neuroblastoma and other peripheral nerve cell tumors (NB-PNT) are the most common extracranial solid tumors in children. This study aimed to describe the global burden of NB-PNT across different age groups and genders, including incidence, prevalence, mortality, and disability-adjusted life years (DALYs) in various countries and regions. Additionally, we analyzed changes in the disease burden over the past three decades and predicted future trends up to 2036. Methods Using open data from the Global Burden of Disease (GBD) database (1990–2021), we provided a dynamic description of the disease burden of NB-PNT patients across different age and gender groups on a global scale. Joinpoint analysis was used to calculate the average annual percentage change (AAPC) to quantify trends in the burden of NB-PNT. Meanwhile, the Bayesian Age-Period-Cohort (BAPC) model was applied to predict the changes in disease burden up to 2036. Results From 1990 to 2021, the global burden of NB-PNT increased significantly, with global prevalence rising from 41,456 to 56,326 cases. Gender and age disparities were evident, with male patients and patients aged 6–11 months exhibiting higher disease burden. Regional variations were observed, with higher disease burdens in regions with a higher sociodemographic index (SDI), although low-SDI regions showed a consistent upward trend. Overall, the prevalence of NB-PNT increased year by year (overall AAPC = 0.64% [0.56 − 0.72%]), with a slight decline in age-standardized mortality rates observed in 2019 (APC2019 − 2021 = -2.02%). Projections indicate a slight decline in both incidence and mortality rates by 2036, with a more pronounced reduction in females. Conclusions A higher burden of NB-PNT was evident among male patients and infants. The disease burden in low-SDI regions has increased in recent years, while a decline was observed in high-SDI regions. Over the past 30 years, the burden rose overall, although a decline in incidence was observed in 2019. Projections indicate a slight decrease in global incidence and mortality rates through 2036.